2005
DOI: 10.1186/1471-2296-6-44
|View full text |Cite
|
Sign up to set email alerts
|

A framework to evaluate research capacity building in health care

Abstract: BackgroundBuilding research capacity in health services has been recognised internationally as important in order to produce a sound evidence base for decision-making in policy and practice. Activities to increase research capacity for, within, and by practice include initiatives to support individuals and teams, organisations and networks. Little has been discussed or concluded about how to measure the effectiveness of research capacity building (RCB)DiscussionThis article attempts to develop the debate on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
450
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(469 citation statements)
references
References 26 publications
6
450
1
12
Order By: Relevance
“…The interview questions and probes were drawn from a previous study and from literature around research capacity building strategies. [1,2,5,6,22] Research personnel conducted, digitally recorded, and transcribed the focus group and/or interview sessions. A series of 7 interviews (note a few had more than one participant) were held to accommodate the issues with scheduling.…”
Section: Recruitment Of Study Participants and Data Collection Procedmentioning
confidence: 99%
See 2 more Smart Citations
“…The interview questions and probes were drawn from a previous study and from literature around research capacity building strategies. [1,2,5,6,22] Research personnel conducted, digitally recorded, and transcribed the focus group and/or interview sessions. A series of 7 interviews (note a few had more than one participant) were held to accommodate the issues with scheduling.…”
Section: Recruitment Of Study Participants and Data Collection Procedmentioning
confidence: 99%
“…[1][2][3] Over the last decade, several research capacity assessment and strategies have been undertaken. [4][5][6][7][8][9][10][11][12] Research capacity is a process of individual and institutional development that leads to higher levels of competencies and capabilities to perform useful research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such disciplines have a low research skills base and may lack the research infrastructure needed to develop knowledge for evidence-based practice (Ilott 2004). Further, research in these disciplines is usually self-funded and less likely to be published in peer-reviewed journals (Cooke 2005).…”
Section: Consulting the Literaturementioning
confidence: 99%
“…Evidence informed policy making depends on the capacity of policy makers to use such reviews and the capacity of researchers to produce them. That each of these capacities needs the other is apparent for research about both health (Cooke 2005) and international development (Bates et al 2006); and has been shown to be applicable to the production of systematic reviews (Oliver et al 2015a). These capacities need to be matched by timeliness and relevance of evidence to inform policy dilemmas (Oliver K et al 2014;Whitty 2015).…”
Section: Introductionmentioning
confidence: 99%